5-Iodo-2-arylalkylthio-6-aryl pyrimidin-4(3H)-ones as non-nucleoside anti-HBV agents1. Issue 8 (5th August 2015) - Zhang, Yu; Sun, Xuefeng; Fan, Ningning; Zhao, Jianxiong; Tu, Jing; Chen, Xiangmei; Liu, Junyi; Wang, Xiaowei
<x xml:space="preserve">Abstract</x> Pyrimidone derivatives have been synthesized and evaluated as anti-HBV agents, in which two compounds exhibited more potent activity than lamivudine.